The Flowing of the Sacred Space: How Reciprocal Exchanges with Deities Are Affected by Urbanization - Cao, Meng (Religions, 2023)
Although there is a consensus on religious revival in China, it must be noted that popular religion and institutional religions such as Buddhism and Daoism adopt different strategies to survive the state’s regulations. Many temples that used to facilitate the worship of local deities have to establish some form of intangible cultural heritage or emphasize the deity’s history and folklore to de-religionize. During this process, a temple may earn its lawful place to survive, but risks its communality in the village. Based on studies of rural and urban temples in Henan and Shandong provinces, in this paper, I attempt to understand people’s religiosity and how they conduct the human–deity exchange under social transformation. Popular religion is characterized by the pursuit of efficacy and its embeddedness in rural life. The traditional binary exchange with deities could be used to maintain a relationship with deities as well as offer urgent solutions, while three-party chains of exchange not only constitute a religious gift economy but also offer a religious agent to seek answers. I argue that temples are marginalized and excluded from village life, so people need to find new means by which to continue their religious practices beyond what the state sponsors, and this has led to the flowing of sacred places.